Learning Strategies To Develop Vocabulary Used By An Eight Grader Of RSBI Of SMPN 2 Karanganyar - Widayanti, Liza (2012)
This research is about learning strategies used by an eighth grader of RSBI program at SMPN 2 Karanganyar to develop vocabulary. The objective of this research is to describe learning strategies used by an eighth grader of SMPN 2 Karanganyar to develop vocabulary that is divided into four aspects, namely 1) learning strategies to understand word meaning, 2) learning strategies to develop pronunciation skill, 3) learning strategies to develop spelling skill, and 4) learning strategies to understand grammar. The setting of this research is SMPN 2 Karanganyar. Then, the type of this research is case study. The subject of this research is an eighth grader at SMPN 2 Karanganyar. The writer uses interview and observation to collect the data. The data analysis technique is from Miles and Huberman theory. The results of this research are separated into four, as follows: 1) The learning strategies used to understand word meaning are 6 meta-cognitive strategies, 11 cognitive strategies, and 2 socio-affective strategies. The metacognitive strategies can be divided into advance organizer, directed attention, self management, functional planning, delayed production, and self evaluation. And the cognitive strategies are repetition, resourcing, translation, grouping, note taking, deducation, imagery, auditory representation, key word, transfer, and inferencing. Then, the socio-affective strategies are cooperation and question for clarification. 2) The learning strategies to develop pronunciation skill are 6 meta-cognitive strategies, 7 cognitive strategies, and 2 socio-affective strategies. The meta-cognitive strategies are advance organizer, directed attention, self management, self monitoring, delayed production, and self evaluation. And the cognitive strategies are repetition, resourcing, grouping, deducation, imagery, auditory representation, and inferencing. Then, the socio-affective strategies are cooperation and question for clarification.3) The learning strategies to develop spelling skill are 4 meta-cognitive strategies, 5 cognitive strategies, and 2 socio-affective strategy. The meta-cognitive strategies are directed attention, self management, delayed production, and self evaluation. And the cognitive strategies are repetition, resourcing, translation, auditory representation, and key word. Then, the socio-affective strategies are cooperation and question for clarification.4) The learning strategies to understand grammar are 5 meta-cognitive strategies, 6 cognitive strategies, and 1 socio-affective strategy. The meta-cognitive strategies are directed attention, self management, functional planning, delayed production, and self evaluation. And the cognitive strategies are resourcing, translation, grouping, note taking, transfer, and inferencing. Then, the socio-affective strategy is question for clarification. The learning strategies that she used to understand word meaning are the most excessive strategy from the other aspects. And the learning strategies that are used to develop spelling skill are the lowest strategy from the other aspects.